Vertical Eddy Diffusivity Parameterization Based on a Large‐Eddy Simulation and Its Impact on Prediction of Hurricane Landfall - Xin Li; Zhaoxia Pu (Geophysical Research Letters)
Abstract The vertical eddy diffusivity (VED) in the planetary boundary layer (PBL) affects tropical cyclones' structure and evolution. Uncertainties of VED in the PBL parametrization scheme of a mesoscale model could be caused by the model's inability to represent large eddies (LEs). Using a large‐eddy simulation (LES) of Hurricane Harvey (2017) as a benchmark, the YSU PBL scheme is improved by adding effects of LEs derived from the LES. It is found that LEs' maximum intensity is linearly significantly related to the square of mean horizontal divergence below 400 m of height at the same air column with a slope coefficient of 1.97. The revised YSU scheme relates the VED of momentum (Km) to the square root of LEs' intensity with a slope coefficient of 0.08 in PBL and 0.20 in a free atmosphere. Compared to the original scheme, the modified YSU scheme leads to improved forecasts of landfalling hurricanes.